Analisis Faktor-Faktor yang Mempengaruhi Permintaan Air pada Perusahaan Daerah Air Minum (PDAM) di Kota Banjarmasin - Rizki, Fahira Amaliana; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to examine variables such as Water user (X1), Water Price (X2), and GRDP Per capita (X3) that affect water demand (Y) at regional drinking water companies (PDAM) in Banjarmasin City. The population in this study is the annual report data conducted at PDAM Bandarmasih. The research method used is descriptive quantitative in the form of data from PDAM Bandarmasih and the Central Statistics Agency. The hypothesis testing used is the classical assumption test and multiple linear regression analysis. The results of this study indicate that the independent variable Waters user (X1), water price (X2), and Income per capita (X3) significantly affect the dependent variable water demand (Y). The varying water price, the dominant factor for the water demand, has a negative effect; if the water quantity increases by 1%, the water demand decreases. The variables X1 and X3 have a positive effect on the water demand (Y) of PDAM Banjarmasin City